Mercury Exposure and Health Effects in Humans: A Systematic Review of Biomarker Evidence - Yulia Khairina Ashar; Wafida Tunnur Siregar; Aprillia Dwi Astuti; Nabila Fatila; Nabila Andini; Chairunnisa Chairunnisa (Dinasti Publisher, 2025)
Mercury remains a long-lasting pollutant in the environment, known for its toxic effects on humans, especially from long-term exposure. This systematic review compiles recent findings on how mercury exposure affects human health, focusing on studies using biological markers. Research articles from 2000 to 2025 were retrieved from PubMed, Scopus, and Web of Science. Included studies were observational or experimental, involving human subjects with mercury detected in blood, hair, or urine, alongside health impact assessments. The review followed PRISMA standards, and risk of bias was evaluated using the Newcastle-Ottawa Scale. Out of all results, 40 studies met the criteria. Most showed increased health risks such as neurotoxic, kidney, and heart problems in people living near gold mining sites, industrial areas, or those frequently eating seafood. Blood and hair were the most used biomarkers. Sensitive groups like pregnant women and children showed greater vulnerability even at low exposure levels. Overall, mercury continues to pose a public health threat, highlighting the urgent need for stricter environmental policies and targeted protective actions.